2008
DOI: 10.1002/anie.200802366
|View full text |Cite
|
Sign up to set email alerts
|

Carboxylate‐Bridged Dinuclear Active Sites in Oxygenases: Diiron, Dimanganese, or is Heterodinuclear Better?

Abstract: bioinorganic chemistry · enzymes · iron · manganese · metalloproteinsCarboxylate-bridged diiron centers are a frequently observed structural motif in biological systems, and the corresponding enzymes catalyze a wide range of important reactions. Within this class of enzymes, a highly interesting family of diiron proteins is characterized by an eye-catching feature in their secondary structure: The dinuclear metal site is localized between a bundle of four a helices (four-helix bundle proteins) that provide coo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…The small energy difference makes the assignment of position 1 for Mn rather uncertain. From arguments about the proximity of position 1 to the electron transfer chain and the observed change exclusively of the oxidation state of MnIV in the activated state, Mn in position 1 is consistent with experiments, as concluded by Roth et al (38) However, for a complete picture, some of the calculations below were also made on a model with Mn in position 2. The difference in energetics between having a higher oxidation state on Fe instead of Mn is larger, 14.4 kcal mol -1 , showing that Mn(IV)Fe(III) is much more stable than Mn(III)Fe(IV), consistent with experiments (15,17).…”
Section: Resultssupporting
confidence: 84%
“…The small energy difference makes the assignment of position 1 for Mn rather uncertain. From arguments about the proximity of position 1 to the electron transfer chain and the observed change exclusively of the oxidation state of MnIV in the activated state, Mn in position 1 is consistent with experiments, as concluded by Roth et al (38) However, for a complete picture, some of the calculations below were also made on a model with Mn in position 2. The difference in energetics between having a higher oxidation state on Fe instead of Mn is larger, 14.4 kcal mol -1 , showing that Mn(IV)Fe(III) is much more stable than Mn(III)Fe(IV), consistent with experiments (15,17).…”
Section: Resultssupporting
confidence: 84%
“…95,[96][97][98][99][100][101] For recent reviews see. [102][103][104][105] Notably, it was shown that the reconstitution reaction proceeds via a Mn(IV)-Fe(IV) Intermediate state. 106 This is interesting because the Fe(IV)-Fe(IV) intermediate has not been observed in standard R2 proteins while it has been observed in 2-electron oxidases such as MMO.…”
Section: Class Ic R2 Proteinsmentioning
confidence: 99%
“…[5][6][7][8] This principle is often exploited for natural small molecule conversion in enzymes. [9][10][11][12] However, the synthesis of heterodinuclear complexes from mononuclear precursors presents a special challenge due to possible disproportionation and selectivity problems resulting in mixtures of symmetric and asymmetric complexes. One way to steer heterodinuclearity is to utilize a ligand backbone with two different binding sites [13] (for the combination Ni/Zn, which is of relevance here see e.g.…”
Section: Introductionmentioning
confidence: 99%